2017
DOI: 10.1161/jaha.117.005997
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural Alterations and Oligodendrocyte Dysmaturation in White Matter After Cardiopulmonary Bypass in a Juvenile Porcine Model

Abstract: BackgroundNewly developed white matter (WM) injury is common after cardiopulmonary bypass (CPB) in severe/complex congenital heart disease. Fractional anisotropy (FA) allows measurement of macroscopic organization of WM pathology but has rarely been applied after CPB. The aims of our animal study were to define CPB‐induced FA alterations and to determine correlations between these changes and cellular events after congenital heart disease surgery.Methods and ResultsNormal porcine WM development was first asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 66 publications
6
18
0
Order By: Relevance
“…Recent animal models of CHD suggest that abnormal cerebral cortical development is secondary to cerebral white matter abnormalities, likely reflecting developmental vulnerability of the developing subplate 2 , 3 . In parallel, recent CHD neuroimaging studies have delineated important subcortical morphological reductions that are not only present in the fetal and preoperative neonatal period, but are also persistent across the lifespan and likely mediate poor neurocognitive outcomes 4 8 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Recent animal models of CHD suggest that abnormal cerebral cortical development is secondary to cerebral white matter abnormalities, likely reflecting developmental vulnerability of the developing subplate 2 , 3 . In parallel, recent CHD neuroimaging studies have delineated important subcortical morphological reductions that are not only present in the fetal and preoperative neonatal period, but are also persistent across the lifespan and likely mediate poor neurocognitive outcomes 4 8 .…”
Section: Discussionmentioning
confidence: 99%
“…However, the relationship between subcortical morphology and white matter/subplate vulnerability has not been studied in detail in infants with CHD. Hypoxia associated with congenital heart disease reduces proliferation and neurogenesis in the subplate structures and developing white matter, thus reducing long-term growth of both cortical and likely also subcortical structures 2 , 3 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our previous studies have demonstrated that CPB and circulatory arrest-induced brain insults resulted in apoptosis and dysmaturation of oligodendrocyte lineage and microglia expansion. 20,21,36 In the damaged rodent white matter, MSCs promote endogenous proliferation and differentiation of oligodendrocyte progenitors. 17,37 Administration of MSCs also regulates microglia activation after hypoxic-ischemic brain injury.…”
Section: Commentmentioning
confidence: 99%